Harms and Benefits of Using Aspirin for Primary Prevention of Cardiovascular Disease: A Narrative Overview - Lippi, Giuseppe; Danese, Elisa; Favaloro, Emmanuel J. (Seminars in Thrombosis and Hemostasis, 2019)
Aspirin is one of the most often used drugs for prevention and treatment of a variety of thrombotic disorders. This narrative review aims to provide an overview of evidence highlighting potential benefits and relative harms of aspirin in primary prevention of cardiovascular disease. The authors summarize key findings of the ASPirin in Reducing Events in the Elderly (ASPREE) Investigator Group randomized trial and also provide a comparative overview of recent meta-analyses. Overall, all-cause mortality was largely heterogeneous, with some meta-analyses showing a modestly decreased risk in patients taking aspirin, with others reporting no effects, but the ASPREE Investigator Group trial evidencing 14% higher risk. Regarding cardiovascular disease, the most favorable impact could be noted for major adverse cardiovascular events, with most meta-analyses reporting a decreased risk in people receiving aspirin. Conversely, the ASPREE Investigator Group trial demonstrated no significant impact of aspirin on risk of cardiovascular mortality or ischemic stroke. A modest favorable effect of aspirin in decreasing the risk of myocardial infarction was noted in two meta-analyses, but not in other reports or in the ASPREE Investigator Group trial. Furthermore, one meta-analysis reported a lower risk of future cancer, others failed to report a significant effect, and the ASPREE Investigator Group trial reported a 31% increased risk. Unlike these conflicting outcomes, the bleeding risk of patients receiving aspirin was found to be consistently enhanced in all reports reviewed. These recent findings would lead us to conclude that the harms of aspirin in primary prevention of cardiovascular disease may be larger than the benefits, especially in the elderly general population.
Keywords: aspirin; cardiovascular disease; mortality; cancer; prevention